The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1002/cjce.5450610412
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature oxidation of athabasca bitumen

Abstract: The kinetics of low temperature oxidation in the Athabasca oil sands were investigated over the temperature range 373 K to 459 K. Oxidation experiments, in which the sand‐free bitumen was vigorously stirred to obtain a homogeneous oxygen concentration throughout the bitumen, were carried out. It was concluded that the oxidation reaction is governed by three different kinetic expressions depending on temperature and past oxidation history. These are: (i) a high rate first order regime which is obeyed at low ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…At 150°C, there is change in reaction order. There is a high-rate first-order autoxidation regime below 150°C and second-order autoxidation regime at low extent of oxidation at temperatures above 150°C (Babu and Cormack 1983). For example, compared with a straight run kerosene fraction where thiol removal increases with oxidation temperature, sulfur removal from bitumen does not monotonically increase with autoxidation temperature (Paniv et al 2006).…”
Section: Autoxidationmentioning
confidence: 99%
“…At 150°C, there is change in reaction order. There is a high-rate first-order autoxidation regime below 150°C and second-order autoxidation regime at low extent of oxidation at temperatures above 150°C (Babu and Cormack 1983). For example, compared with a straight run kerosene fraction where thiol removal increases with oxidation temperature, sulfur removal from bitumen does not monotonically increase with autoxidation temperature (Paniv et al 2006).…”
Section: Autoxidationmentioning
confidence: 99%
“…The change at ∼150 °C coincided with a reported change in bitumen oxidation selectivity. 10,16 (c) There was an increase in the oxygenate functionality in the oxidized bitumen. An increase in both C−O and CO bonds were apparent from infrared spectroscopy, with some increase in SO bonds also being noted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on low-temperature bitumen oxidation also indicated that there is a change in the oxidation selectivity and kinetics at ∼150 °C. 10,16 The effect of oxidation temperature on the properties of oxidized bitumen was investigated by performing oxidation for only 6 h at 140, 150, and 160 °C. The mass loss observed was in the range of 0.6−0.8 wt %.…”
Section: Extended Autoxidation Of Bitumen At 130 °Cmentioning
confidence: 99%
See 2 more Smart Citations